Minimally invasive short segment pedicle screw fixation for Thoraco-Lumbar Trauma: Where we stand? - Vipin Kumar Gupta; Arvind malhora; Ashwani kumar (Nepal Journal of Neuroscience, 2022)
Background & Overview of Literature: Use of MISS or Percutaneous pedicle screws for thoracolumbar trauma has shown superiority in terms of postoperative pain, blood loss, operating time, hospital stay and incision size as compared to open surgical method. The use of MISS in thoracolumbar trauma has been limited due to the high cost and lack of posterolateral fusion. There is conflicting evidence for and against the use of MISS in AO spine A3/A4 fractures without any neurological deficit and maybe managed conservatively as well. Purpose: To establish efficacy and safety of MISS, short segment pedicle screw fixation in patients of thoraco-lumbar fractures but without any neurological deficit. Study Design: Retrospective case reports of 2 years in which 20 patients of thoraco-lumbar trauma that underwent minimally invasive short segment spine fixation were included. Material & Methods: Retrospective analysis of 20 patients of thoraco-lumbar spine fractures that were operated from 2017 to 2019 at Government Medical College & Hospital, Chandigarh. Patients included were in the age group of 23-70 years, operated within one week of trauma, AO type A3 and A4, and operated using short segment fixation. Our exclusion criteria were trauma more than one week old, multiple levels of fractures and non-traumatic fractures. Clinical and radiological data were collected and tabulated. Results: Most patients (8 out of 20) had fracture of D12 vertebra. 18 out of 20 patients were involved in a road traffic accident. The mean blood loss was 25.78 mL. Cobb’s angle was used to measure focal deformity and the average gain in Cobb’s angle after surgery was 10.9°. Mean loss in correction was 2.35°. All patients were pain-free after 6 months as measured on the VAS score. The average time taken in getting back to work after surgery was 26 days. Conclusion: MISS is the ideal treatment of choice in patients of thoraco-lumbar spine trauma without any neurological deficit. MISS provides higher safety, early mobilization, less blood loss during surgery, shorter recovery time, and less post-operative pain.